1968
DOI: 10.1002/zaac.19683570410
|View full text |Cite
|
Sign up to set email alerts
|

Die Kristallstruktur von Stickstofftrijodid‐1‐Ammoniak NJ3 · NH3

Abstract: NJ3 · NH3 kristallisiert monoklin in der zentrosymmetrischen Raumgruppe P21/m. Die Elementarzelle mit den Abmessungen a = 7,132 Å, b = 7,506 Å, c = 6,324 Å und β = 98,6° enthält 2 Formeleinheiten NJ3 · NH3. Die Kristallstruktur wurde mit Hilfe dreidimensionaler PATTERSON‐ und Differenz‐FOURIER‐Synthesen aufgeklärt und nach der Methode der „kleinsten Quadrate”︁ bis auf einen Zuverlässigkeitsindex von 5,6% verfeinert. Die NJ3 · NH3‐Struktur baut sich nicht aus isolierten Molekeln auf, sondern enthält als wesentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

1971
1971
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 9 publications
1
9
0
3
Order By: Relevance
“…Although previous work suggested formulas between (NI 3 ) x (NH 3 ) y ( x =1–5, y =0–3), Silberrad demonstrated that the ultimate product is the 1 : 1 adduct NI 3 ⋅NH 3 . The crystal structure of this adduct was reported by Hartl, Bärnighausen, and Jander in 1968, who demonstrated that the compound is composed of −NI 2 −I−NI 2 −I− chains separated by discrete NH 3 molecules. These remaining NH 3 molecules cannot be removed by physical means.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Although previous work suggested formulas between (NI 3 ) x (NH 3 ) y ( x =1–5, y =0–3), Silberrad demonstrated that the ultimate product is the 1 : 1 adduct NI 3 ⋅NH 3 . The crystal structure of this adduct was reported by Hartl, Bärnighausen, and Jander in 1968, who demonstrated that the compound is composed of −NI 2 −I−NI 2 −I− chains separated by discrete NH 3 molecules. These remaining NH 3 molecules cannot be removed by physical means.…”
Section: Introductionmentioning
confidence: 79%
“…After each molecule is fully optimized, a predicted enthalpy of formation can be determined and some bond energies estimated. Table 2 shows the results for NI 3 . Because even a small molecule like NI 3 has several structural parameters, the energy changes depend on what is varied first; in this case, bond lengths versus bond angles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Die PNBindungslänge von 159,1 pm entspricht dem Er w artungsw ert einer D oppelbindung, für die der Be reich von 156 -164 pm angegeben w ird [16]. Auch die N -I-B indung ist mit 205,6 pm relativ kurz, ver glichen m it der term inalen N -I-B indung des po lym eren N I3 N H 3 (215 pm [17]) und mit dem Ergebnis von A b-initio-R echnungen an gasförm i gem IN 3 (213 pm [15,18] …”
Section: Ergebnisseunclassified